Effect of resource availability on evolution of virulence and competition in an environmentally transmitted pathogen. Issue 5 (5th April 2018) - Pulkkinen, Katja; Pekkala, Nina; Ashrafi, Roghaieh; Hämäläinen, Dorrit M; Nkembeng, Aloysius N; Lipponen, Anssi; Hiltunen, Teppo; Valkonen, Janne K; Taskinen, Jouni
Abstract: Understanding ecological and epidemiological factors driving pathogen evolution in contemporary time scales is a major challenge in modern health management. Pathogens that replicate outside the hosts are subject to selection imposed by ambient environmental conditions. Increased nutrient levels could increase pathogen virulence by pre-adapting for efficient use of resources upon contact to a nutrient rich host or by favouring transmission of fast-growing virulent strains. We measured changes in virulence and competition in Flavobacterium columnare, a bacterial pathogen of freshwater fish, under high and low nutrient levels. To test competition between strains in genotype mixtures, we developed a quantitative real-time PCR assay. We found that a virulent strain maintained its virulence and outcompeted less virulent strains independent of the nutrient level and resource renewal rate while a less virulent strain further lost virulence in chemostats under low nutrient level and over long-term serial culture under high nutrient level. Our results suggest that increased outside-host nutrient levels might maintain virulence in less virulent strains and increase their contribution to epidemics in aquaculture. The results highlight a need to further explore the role of resource in the outside-host environment in maintaining strain diversity and driving evolution of virulence among environmentally growing pathogens. Abstract : Virulent strains of an environmentally growing fish pathogen, Flavobacterium columnare, are not affected by outside-host nutrient availability, but less virulent strains decrease in virulence while evolving under low nutrient conditions.